Transition metal coordination polymer-derived materials for supercapacitor applications: recent advances and future perspectives - Saifullahi Kabiru Sa’adu; Cheng Seong Khe; Muhammad Fadhlullah Abd. Shukur; Kwok Feng Chong; Chin Wei Lai; Kok Yeow You; Nik Roselina Nik Roseley; Eslam Aboelazm (Royal Society Open Science)
With the rising demand for efficient, sustainable and scalable energy storage, researchers are continuously exploring innovative materials for next-generation supercapacitors. Among these, transition metal coordination polymer (TMCP)-derived materials have emerged as promising candidates due to their high porosity, redox activity and structural adaptability. These materials offer significant potential for energy storage, but challenges like low electrical conductivity, structural instability and limited charge retention have restricted their widespread application. To overcome these hurdles, researchers have developed transformation strategies such as carbonization, phosphorization, sulfidation and oxide formation, enhancing the conductivity, stability and overall electrochemical performance of TMCPs. This review investigates the latest breakthroughs in TMCP-derived electrode materials, highlighting key advancements in synthesis techniques, structural engineering and hybrid material integration to improve charge transport and long-term durability. The incorporation of green chemistry principles, such as low-temperature synthesis, the use of non-toxic precursors, and strategies for recycling or reducing harmful byproducts, is highlighted, consequently promoting the fabrication of environmentally friendly supercapacitors. Furthermore, it explores how nanostructured designs and composite materials are unlocking new possibilities for high-performance supercapacitors. It also provides a perspective on the future of TMCPs in energy storage by fusing theoretical insights with experimental evidence. Theoretical frameworks like density functional theory and emerging machine learning models are other methods employed to better understand redox behaviour and drive material design. It addresses present issues and suggests viable future directions for their useful application.